The Role of Visual Acuity and Segmentation Cues in Compound Word Identification - Hyönä, Jukka (Frontiers Research Foundation, 2012)
Studies are reviewed that demonstrate how the identification of compound words during reading is constrained by the foveal area of the eye. When compound words are short, their letters can be identified during a single fixation, leading to the whole-word route dominating word recognition from early on. Hence, marking morpheme boundaries visually by means of hyphens slows down the processing of short words by encouraging morphological decomposition when holistic processing is a feasible option. In contrast, the decomposition route dominates the early stages of identifying long compound words. Thus, visual marking of morpheme boundaries facilitates processing of long compound words, unless the initial fixation made on the word lands very close to the morpheme boundary. The reviewed pattern of results is explained by the visual acuity principle (Bertram and Hyönä, 2003) and the dual-route framework of morphological processing.